Factors associated with testing positive for syphilis among MSM who present as sexual contacts of syphilis from a clinic-based population. (19th April 2021) - Richardson, Daniel; Pickering, Alice; Nichols, Kayleigh; Buss, Zoe; Trotman, Daniel; Fitzpatrick, Colin; Williams, Deborah
Abstract : Objectives: There has been a significant increase in syphilis in men who have sex with men (MSM) in the UK over the past 20 years. Partner notification strategies have increased the number of MSM attending STI clinics as sexual contacts of syphilis. Current guidelines suggest testing and consideration of presumptive antimicrobial treatment. Syphilis treatment with benzathine penicillin requires clinic resources, is painful and is associated with complications. It is important we consider strategies to rationalise presumptive antimicrobial use and promote antimicrobial stewardship. Methods: We aimed to determine if there are any factors associated with having syphilis among MSM attending as sexual contacts of syphilis in a cross-sectional study. We examined the clinical records of MSM attending as sexual contacts of syphilis from January to December 2019. Results: Of the 6613 MSM who attended for STI testing, 142 of 6613 (2.1%) presented as sexual contacts of syphilis. The median age was 40 years (IQR=31–51), 43 of 142 (30%) were HIV positive, 38 of 142 (27%) had been diagnosed and treated for syphilis in the past, and 11 of 142 (8%) presented with symptoms (possible lesions of primary or secondary syphilis). Thirteen (9%, 95% CI=4.4 to 13.9) tested positive for syphilis on the day of presentation. MSM who were symptomatic (genital ulcer or body rash), HIV positive or had a history of syphilis were significantly more likely to test positive for syphilis (OR=51.88, 95% CI: 3.01 to 893.14, p=0.007). Conclusions: We have shown that in our clinic-based population of MSM who presented as sexual contacts of syphilis, the factors associated with testing positive for syphilis were: having HIV, having a history of syphilis or presenting with symptoms (possible lesions of primary or secondary syphilis). These factors could be used to rationalise antibiotic treatment among MSM presenting as sexual contacts of syphilis. Further research is needed to validate this finding in other populations of MSM and people affected by syphilis.